2004
DOI: 10.1021/ja0451968
|View full text |Cite
|
Sign up to set email alerts
|

Orientational Control of Electronic Coupling in Mixed-Valence, Binuclear Ruthenium(II)−Bis(2,2‘:6‘,2‘ ‘-Terpyridine) Complexes

Abstract: A series of binuclear ruthenium(II)-bis(2,2':6',2' '-terpyridine) complexes has been prepared around a central biphenylene unit equipped with a strap of variable length. Partial oxidation forms the mixed-valence complex that displays both ligand-to-metal, charge-transfer, and intervalence charge-transfer (IVCT) transitions in the near-IR region. On the basis of Hush theory, the electronic coupling matrix element for interaction between the metal centers decreases with increasing length of the tethering strap. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 21 publications
(24 reference statements)
3
55
0
Order By: Relevance
“…The magnitude of the electronic coupling between the terminal chromophores shows ap recise dependence on the dihedral angle around ab ridging biphenyl group, controlled by selecting the bound cations. [55][56][57] Recently,V enkataraman et al [46] and Wandlowski et al [47][48][49][50][51][52] reported the influence of f on changes in the singlemolecule conductivity in substituted biphenyls or conformationally constrained biphenyls in which the biphenyl rings are connected by a( CH 2 ) n link at the 2-and 2'-positions.O nt wisting of the biphenyl system from coplanar (f= 08)t op erpendicular (f= 908), the conductance decreased by af actor of 30. [48] However,r eports of systematics tudies on the influence of f on the electronic coupling and redox processes of bimetallic complexes [ML n (bridge)ML n ] are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of the electronic coupling between the terminal chromophores shows ap recise dependence on the dihedral angle around ab ridging biphenyl group, controlled by selecting the bound cations. [55][56][57] Recently,V enkataraman et al [46] and Wandlowski et al [47][48][49][50][51][52] reported the influence of f on changes in the singlemolecule conductivity in substituted biphenyls or conformationally constrained biphenyls in which the biphenyl rings are connected by a( CH 2 ) n link at the 2-and 2'-positions.O nt wisting of the biphenyl system from coplanar (f= 08)t op erpendicular (f= 908), the conductance decreased by af actor of 30. [48] However,r eports of systematics tudies on the influence of f on the electronic coupling and redox processes of bimetallic complexes [ML n (bridge)ML n ] are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] The coordination bond can be tuned by external conditions, such as pH value and temperature. Herein, we present a study of a hydrogen-bonded supramolecular network using bis(2,2':6',2"-terpyridine)-4'-oxyhexadecane (BT-O-C16), the molecular structure of which is shown in Figure 1 a.…”
Section: Introductionmentioning
confidence: 99%
“…[9] The difference is significantly more pronounced than that found previously for hole transfer through related systems, for which the coupling element increased by a factor less than twofold on moving from orthogonal to coplanar geometries. [26] This latter finding might be suggestive of the possibility that different electronic processes have disparate sensitivities towards such angular effects. If correct, this would be a most important finding, because it would provide the opportunity to employ such angular constraints as a means by which to discriminate between rates of forward and reverse electron transfer in molecular dyads.…”
mentioning
confidence: 96%